The correlation between body conception and actual body mass index among adolescents: some variables and their role - Yardimci, Hülya; Hakli, Gülperi; Çakiroğlu, Funda Pınar; Özçelik, Ayşe Özfer (Progress in Nutrition, 2016)
Summary. Objective: This study aimed to determine the relationships between adolescents’ actual body mass indices BMIs and their body image perceptions and how they vary by gender and age. Subjects and Methods: The questionnaire which has two sections includes general information about the students and the Stunkard Figure Rating Scales. Gender and age were used as explanatory variables. The research data were analyzed using SPSS statistical software. Statistical analyses included factor analysis and Cohen’s kappa test (K) A criterion alpha level of <.001 was used to determine statistical significance. Results: A total of 321 students participated in the study; of these, 58.6% were boys, 41.4% were girls. The mean age was 14.6±1.2 years old. The difference by age and gender groups between the real BMIs of adolescents, the BMIs they perceived and the perceptions of others was significant and the compatibility between their real BMIs and the BMIs they perceived are at the medium level (p=0.000). The compatibility of the perception which figure they were regarded by others with their real BMI perceptions are in medium level for boys for the age group of 12-14 whereas poor level for girls and for the age group of 15-18 (p=0.000). Conclusions: This study found that adolescents had misconceptions about their real weights, about the weights they wanted to be and about their perceptions of others’ views of their weights. Age and gender were effective factors in these perceptions.